Poems of Guido Gezelle A Bilingual Anthology - Vincent, Paul (UCL Press, 2016)
The Bruges-born poet-priest Guido Gezelle (1830-1899) is generally considered one of the masters of nineteenth-century European lyric poetry. At the end of his life and in the first two decades of the twentieth century, Gezelle was hailed by the avant-garde as the founder of modernFlemish poetry. His unique voice was belatedly recognised in the Netherlandsand often compared with his English contemporary Gerard Manley Hopkins (1844-1889).In this bilingual anthology, award-winning translator Paul Vincent selects a representative picture of Gezelle's output, from devotional through narrative, to celebratory and expressionistic. Gezelle's favourite themes are childhood, the Flemish landscape, friendship, nature, religion and the Flemish vernacular, and his apparently simple poems conceal a sophisticated prosody and a dialogue with spiritual and literary tradition.